Studies on the physico-chemical parameters of reservoir at Dhanegoan district Osmanabad (M.S.), India. - Pawar, S B; Shembekar, V S (Journal of Experimental Sciences, 2012)
The present study deals with assessment of some physico-chemical parameters of reservoir at Dhanegoan, District Osmanabad (M.S.), India. The physico-chemical characteristics were studies and analyzed during August 2009 to July 2010. Seasonal variation at four different Sampling Sites of the Reservoir at Dhanegoan, were observed. The results revealed that the condition of this reservoir in different months showed seasonal wise fluctuation in the Physico-chemical parameters.